Targeting BET Proteins With a PROTAC Molecule Elicits Potent Anticancer Activity in HCC Cells - Zhang, Huapeng; Li, Gongquan; Zhang, Yi; Shi, Jihua; Yan, Bing; Tang, Hongwei; Chen, Sanyang; Zhang, Jiakai; Wen, Peihao; Wang, Zhihui; Pang, Chun; Li, Jie; et al. (Frontiers in Oncology, 2020)
Background and Aim: Bromodomain and extraterminal domain (BET) family proteins are epigenetic regulators involved in human malignances. Targeting BET proteins for degradation using proteolysis-targeting chimera (PROTAC) recently has drawn increasing attention in the field of cancer therapeutics. BET proteins have been found to be overexpressed in HCC cells and tumor tissues. However, the biological activity of BET-PROTACs in hepatocellular carcinoma (HCC) remains unclear. In this study, we investigated anti-HCC activity of BETd-260, a BET-PROTAC molecule using in vitro and in vivo models. Methods: BETd-260-mediated anti-HCC activity was investigated by cell viability, apoptosis assays. Efficacy was examined with a cell lines-derived HCC xenograft model in mice. Anticancer mechanism was investigated by RT-PCR, western blotting and immunohistochemical staining. Results: BETd-260 potently suppressed cell viability and robustly induced apoptosis in HCC cells. BETd-260 reciprocally modulated the expression of several apoptotic genes in HCC cells, i.e. suppressing the expression of anti-apoptotic Mcl-1, Bcl-2, c-Myc and X-linked inhibitor of apoptosis (XIAP), whereas increasing the expression of pro-apoptotic Bad. BETd-260 treatment led to disruption of mitochondrial membrane integrity, and triggered apoptosis via intrinsic signaling in HCC cells. BETd-260 triggered apoptosis in HCC xenograft tissue and profoundly inhibited the growth of HCC xenograft tumors in mice. Conclusion: Our data suggest that pharmacological targeting of BET for degradation may be a novel therapeutic strategy for the treatment of HCC.